A avaliação da aprendizagem no modelo da progressão continuada - Freitas, Sandro Tadeu de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The objective of this work is to understand the evaluation of learning in the system of Continued Progression as present by Deliberation of CEE No. 09/97. Therefore, we approach the conception of the evaluation of learning from the point of view of researchers who work in the area of Mathematics Education. Also, we seek to know the legislation pertinent to the subject finding in the Law of Guidelines and Bases of National Education (LDB) and in the Curriculum of the State of São Paulo works that are articulated with the readings made researchers about the evaluation. Understanding this conception of evaluation, we look for in two State Public Schools of a city of São Paulo, to see how the teachers have treated the evaluation of the learning in the classroom. We have seen that although they understand the meaning of Continuous Progression, the modes of treatment of evaluation are distinct

Este trabalho tem como objetivo compreender a avaliação da aprendizagem no sistema da Progressão Continuada tal qual é exposta na Deliberação CEE nº09/97. Para tanto, abordamos a concepção da avaliação da aprendizagem do ponto de vista dos pesquisadores que atuam na área da Educação Matemática. Ainda, buscamos conhecer a legislação pertinente ao assunto encontrando na Lei de Diretrizes e Bases do Estado de São Paulo (LDB) e no Currículo do Estado de São Paulo, referências que nos levam ao exposto pelos pesquisadores acerca da avaliação. Entendendo esta concepção de avaliação, buscamos em duas escolas publicas estaduais de um município paulista, ver como os professores têm tratado a avaliação da aprendizagem em sala de aula. Vimos que embora, compreendam o sentido da progressão continuada, os modos de tratamento da avaliação são distintos
Keywords: Matemática - Estudo e ensino; Professores - Formação; Avaliação; Mathematics Study and teaching